Penerapan Teknik Role Playing melalui Konseling Kelompok dalam Meningkatkan Interaksi Sosial Siswa SMP Negeri 1 Salomekko - Lisnawati Lisnawati; Sulaiman Samad; Rosmini Rosmini (Indonesian Journal of School Counseling: Theory, Application, and Development, 2022)
This study aims to help improve students' social interaction through group counseling services using role playing techniques for students of SMP Negeri 1 Salomekko. This study uses the type of research PTBK (Counseling Action Research) with two cycles, namely cycle I and cycle II consisting of planning, action, observation, reflection and evaluation stages. Collecting data to capture students who have low social interaction by using a social interaction questionnaire, in the form of an ordinal scale in the form of a Likert scale. The subjects of this study were 6 students who had low student social interaction relationships. Data analysis was used by percentage analysis technique. The results showed that there was an increase in students' social interaction after the provision of group counseling services using the role playing technique. In the first cycle, the results of the increase in students' social interaction were 45%. And in the second cycle, the results of the increase in students' social interaction were getting better to 80.3%. So it can be concluded that the role playing group counseling service can increase the social interaction of the students of SMP Negeri 1 Salomekko